O mundo equilibrado pelos demônios e pela ciência além dela - Andrade, Matheus Martin de (Universidade Federal de São Carlos, 2023)
Introduction: During the COVID-19 pandemic, concerns have arisen about aerosol-generating procedures and the transmission of the virus to healthcare professionals during these practices. Several airway management procedures fit into this classification, however, they are primary for the care of critical patients, with no possibility of suspension or postponement when facing a respiratory virus pandemic. In this context, several technologies have been proposed to reduce the risk of contagion in hospital and out-of-hospital health services. Objectives: This systematic review sought to analyze the safety of healthcare professionals during advanced airway management procedures, comparing emerging technologies with traditional techniques. A detailed analysis of existing literature was carried out, evaluating the impacts of technologies on the spread of respiratory pathogens. Materials and methods: This study followed the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), covering searches in Medline, Embase and Web of Science databases in English, Portuguese and Spanish. Three studies were included after an initial search of 1696 articles. Results included epidemiological studies, retrospective studies, and clinical trials. Results: It was identified that many proposals for new techniques were not tested on real patients or lacked control groups for comparison. This review revealed technical challenges in directly measuring the reduction in the risk of healthcare professionals contracting COVID-19 during intubation procedures. Literature presented inconsistencies regarding the increased risk associated with intubation, especially when adequate personal protective equipment (PPE) is used. As for the selected articles, all presented a high risk of bias, in addition to no technique having simultaneously discussed its effectiveness and safety. Discussion: The methodological limitations of the selected studies are highlighted, pointing to the urgency of the pandemic as a factor that compromised the quality of scientific evidence. The abundance of studies proposing new techniques without rigorous testing raises doubts about their clinical usefulness. Conclusion: The pandemic boosted scientific production related to safety in airway management, without, however, being accompanied by a critical view of the quality of what should be published.
The word balanced by demons: by science and beyond it
Keywords: COVID-19; Aerossóis; Intubação; Manuseio das vias aéreas; Equipamentos de proteção; COVID-19; Aerosols; Intubation; Airway management; Protective devices; CIENCIAS DA SAUDE::MEDICINA::CLINICA MEDICA::DOENCAS INFECCIOSAS E PARASITARIAS